Case report: De novo variant of SETD1A causes infantile epileptic spasms syndrome - Lan, Mingping; Wang, Yanjuan; Li, Sixiu; Zhao, Lili; Liu, Ping; Hu, Wenguang (Frontiers in Neurology, 2023)
Infantile epileptic spasms syndrome (IESS) is one of the most common epileptic encephalopathies of infancy, with typical clinical features defined by a triad of epileptic spasms, hypsarrhythmia, and developmental delay. Genetic factors are important causes of IESS. The SETD1A (SET Domain Containing 1A) gene encodes a histone lysine methyltransferase that activates gene transcription through histone H3 lysine K4 methylation. Mutations in the SETD1A gene have been associated with schizophrenia, and some have been reported to cause seizures. Herein, we report a case of IESS caused by a SETD1A gene mutation. Video electroencephalography showed hypsarrhythmia. No specific findings were obtained after brain MRI and metabolic work-up. The seizures disappeared after treatment with adrenocorticotropic hormone, vitamin B6, and valproic acid during hospitalization. Genetic testing revealed that the child had a variant (NM_014712.3:c.3005_3,006 delAG, p.Glu1002Glyfs*20) in exon 12 of the SETD1A gene, representing a de novo mutation. There have been no previous reports on the SETD1A gene causing infantile spasms. We also summarize the existing literature on SETD1A gene–related epilepsy to provide a reference for clinical diagnosis and treatment.